Leading and following in Australian regional development: Why governance matters. Issue 2 (5th September 2019) - Eversole, Robyn; Walo, Megerssa
Abstract: This paper explores challenges and opportunities of place‐based regional development leadership in the Australian context. Drawing on primary data from the recent Australian Government Inquiry into Regional Development and Decentralisation, an analysis of narratives from regional development organizations reveals governance tensions grounded in a deep cultural divide between capital cities and the regions collectively known as "Regional Australia." As regional development organizations describe how State and Federal policy relates to their own diverse regional contexts, they highlight missed opportunities and illustrate how current governance arrangements limit the room to manoeuvre of place‐based regional development leadership. Resumen: Este artículo explora los desafíos y las oportunidades del liderazgo de desarrollo regional basado en la localización en el contexto australiano. A partir de datos primarios de la reciente encuesta del Gobierno australiano sobre el desarrollo regional y la descentralización, un análisis de las narrativas de las organizaciones de desarrollo regional revela tensiones en materia de gobernanza basadas en una profunda división cultural entre las capitales y las regiones conocidas colectivamente como la "Australia Regional". A medida que las organizaciones de desarrollo regional describen cómo se relacionan las políticas estatales y federales con sus propios diversos contextos regionales, ponen de relieve las oportunidades perdidas e ilustran la forma en que las actuales disposiciones de gobernanza limitan el margen de maniobra del liderazgo de desarrollo regional basado en la localización. 抄録: 本稿は、オーストラリアにおける、地域に根ざした発展のリーダーシップの課題と機会を検討する。最近実施された「オーストラリア政府による地域開発と地方分散化に関する調査 (Australian Government Inquiry into Regional Development and Decentralisation)」の主要データを用いて地域開発組織の報告を分析することにより、主要都市とRegional Australia (オーストラリアの地方エリア)といわれる地域との文化的な大きな隔たりに根ざした政治的緊張があることが明らかになった。地域開発組織は、州政府の政策と連邦政府の政策が、どのように各々の異なる地域的背景に関連付けられているか述べているが、同組織は機会の損失を強調し、現在の行政管理体制が地域に根ざした発展のリーダーシップを執る余地をどのように制限しているかを説明している。